Data Analitik Audit: Kontribusi Dan Hambatan Pada Praktik Audit - Fahmi, Muhammad; Harahap, Riva Ubar; Rozi, Facrul (Universitas Islam Islam Sumatera Utara, 2023)
The aim of the study is to determine the contributions and barriers to the use of audit analytical data in audit practice. This study method uses a Systematic Literature Review (SLR) with a bibliometric approach from several relevant journals. The study results reveal that the use of audit analytical data has a positive impact on audit practice, but there are obstacles or barriers to its use such as cognitive bias, inadequate understanding of the use of technology, and implementation costs.